2021
DOI: 10.3390/ijms222112042
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-MS Analysis of Peptide Libraries Expands the Scope of Substrates for Farnesyltransferase

Abstract: Protein farnesylation is a post-translational modification where a 15-carbon farnesyl isoprenoid is appended to the C-terminal end of a protein by farnesyltransferase (FTase). This modification typically causes proteins to associate with the membrane and allows them to participate in signaling pathways. In the canonical understanding of FTase, the isoprenoids are attached to the cysteine residue of a four-amino-acid CaaX box sequence. However, recent work has shown that five-amino-acid sequences can be recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 31 publications
0
26
0
1
Order By: Relevance
“…Gel-shift assay: The assay was performed as previously described (Hildebrandt, Cheng et al 2016, Berger, Kim et al 2018, Schey, Buttery et al 2021. Whole cell lysates of mid log cells were prepared and separated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE; 6% stacking with 9.5% resolving gel) then transferred onto nitrocellulose.…”
Section: Nextmentioning
confidence: 99%
See 2 more Smart Citations
“…Gel-shift assay: The assay was performed as previously described (Hildebrandt, Cheng et al 2016, Berger, Kim et al 2018, Schey, Buttery et al 2021. Whole cell lysates of mid log cells were prepared and separated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE; 6% stacking with 9.5% resolving gel) then transferred onto nitrocellulose.…”
Section: Nextmentioning
confidence: 99%
“…Most of the in vivo reporters used to probe CaaX space have relied on CaaX protein reporters requiring 3-step modification and the superposition of 3 enzyme specificities for their activities (Boyartchuk, Ashby et al 1997, Stein, Kubala et al 2015). Moreover, recent reports demonstrating FTase activity on shortened and extended sequences highlight the flexibility of CaaX substrate lengths, additionally complicating the recognized model of FTase CaaX specificity (Ashok, Hildebrandt et al 2020, Schey, Buttery et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FTIs were initially designed to block oncogenic Ras activity by inhibiting its prenylation, but were discontinued in clinical trials for cancer treatment following the discovery of alternate Ras prenylation pathways [21,22]. However, many FTase substrates exist [23][24][25], leading to the evaluation of FTIs for a wide range of disorders, including cardiovascular disease, hepatitis D and progeria [20,26]. Additionally, FTIs have shown promise towards neurodegenerative diseases characterized by the accumulation of protein aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that proteins terminating in CXXXX or CXX may also potentially be substrates of prenylation. [3][4][5] The third type of prenylation involves geranylgeranyltransferase type II (GGTase-II or RabGGTase) that usually appends two geranylgeranyl units on dual cysteine motifs on proteins, particularly those that belong to the Rab family. These substrates are typically recognized first by the rab escort protein 1 or 2 (REP-1/2) and modified by GGTase-II at their C-terminal cysteines in their -CCXX, -CXC, or -XXCC canonical sequences.…”
Section: Introductionmentioning
confidence: 99%